A reinterpretação da proteção em face da automação prevista na Constituição Federal para que se adeque às necessidades atuais das relações de trabalho - Cornélio, Raphael Lima Lemes (2023)
The theme proposed for the present work aims to demonstrate that the extension of the Constitutional protection against automation, exposed in article 7, XXVII of the CF is not enough to safeguard the labor rights that are impacted by technology. To achieve this goal, the evolution of the term technology will be exposed over time, a term that is metamorphosed and molds itself, to the same extent that it influences the needs of contemporary man. Later, we will point out the impacts caused by technology in labor relations. In sequence, we will analyze whether such impacts caused by technology are part of the current protective scope of article 7, XXVII of the CF, through a study of the existing infraconstitutional legislation. Subsequently, a topic that generates debate in the doctrine is about the effectiveness of fundamental rights in employment relations, and about the discussion between the lack of effectiveness of the article studied, in relation to the position that it defends to be the same self-applicable, under penalty of transforming the Constitution in dead letter. This culminates in a reinterpretation of protection in the face of automation to fit today's needs